1983
DOI: 10.1515/botm.1983.26.4.189
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Influence of Coastal Upwelling and Polluted Rivers on the Microflora of the Northeastern Atlantic off Portugal. II. Activity and Biomass Production of the Bacterial Population

Abstract: During May 1981 the following parameters were measured in the sea area off the west and south coast of Portugal: concentration of monosaccharides, number of actively metabolizing bacteria, maximum uptake velocity and turnover rate of glucose, specific activity rate of the microbial population and bacterial production. A good correlation between the activity parameters was found in all water samples. Highest values of bacterial activity were measured in the region off the mouth of the Tejo River. Apart from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…Bacterial production and abundance in coastal upwelling ecosystems is similar to that reported for other coastal environments and seems to be closely coupled to upwelling cycles (Field et al 1980, Zimmermann et al 1980, Gocke et al 1983, Rheinheimer & Schmaljohann 1983, Hanson et al 1986, McManus & Peterson 1988. In the Benguela upwelling system, BSP has been shown to increase a few days after the peak of PP (Painting et al 1993).…”
Section: Introductionsupporting
confidence: 72%
“…Bacterial production and abundance in coastal upwelling ecosystems is similar to that reported for other coastal environments and seems to be closely coupled to upwelling cycles (Field et al 1980, Zimmermann et al 1980, Gocke et al 1983, Rheinheimer & Schmaljohann 1983, Hanson et al 1986, McManus & Peterson 1988. In the Benguela upwelling system, BSP has been shown to increase a few days after the peak of PP (Painting et al 1993).…”
Section: Introductionsupporting
confidence: 72%
“…Meanwhile, in the southern sections 7 and 9 the phytoplanktonic population had apparently already degenerated and, due to the resulting release of nutrients, a correspondingly large bacterial biomass developed. According to Gocke et al, (1983) the bacterial activity of the further offshore stations in the north was greater than in the corresponding southern stations. The bacterial population of the former, therefore, may still have been in a phase of growth, 'while its development in the latter was more ore less already complete.…”
Section: Discussionmentioning
confidence: 94%
“…The Chlorophyll a content (Gocke et al 1983) could be determined for those samples extracted from the surface region (4-20 m). It fluctuated between 0.05 and 5.6 μg Γ 1 , and the highest value was demonstrated at Station 152.…”
Section: Results ·mentioning
confidence: 99%
“…Although information on bacterioplankton in coastal upwelling ecosystems is scarce, the available data suggest that these systems are not unlike other coastal environments wlth regard to bacterial abundance and activity. Studies of upwelling off Portugal (Gocke et al 1983, Rheinheimer & Schmaljohann 1983, northwest Africa (Zimmermann et al 1980) and southwest Africa (Field et al 1980, Linley & Field 1982 reported bacterial populations on the order of 10' cells 1-l, the great majority of which were not attached to particles. Watson (1978) used indirect methods to estimate that about half of all primary productivity passed through bacteria in coastal upwelling ecosystems.…”
Section: Discussionmentioning
confidence: 98%
“…It has been estimated that 10 to 50 % of primary production passes through the bacterioplankton (Andrews & Williams 1971, Sieburth et al 1977, Hagstrom et al 1979, Fuhrman & Azam 1982 and that bacteria are dividing about 0.2 to 2 d-' (van Es & Meyer-Reil 1982, Ducklow 1983. Recent work in coastal upwelling ecosystems has shown that bacterial abundance is similar to that in other coastal environments and that it varies in response to the upwebng cycle (Field et al 1980, Zimmermann et al 1980, Gocke et al 1983, Rheinheimer & Schmaljohann 1983, Hanson et al 1986.…”
Section: Introductionmentioning
confidence: 99%